2010
DOI: 10.1155/2010/163413
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving Mechanisms for MAC Protocols in Wireless Sensor Networks

Abstract: Energy efficiency is a primary requirement in a wireless sensor network (WSN). This is a major design parameter in medium access control (MAC) protocols for WSN due to limited resources in sensor nodes that include low battery power. Hence a proposed MAC protocol must be energy efficient by reducing the potential energy wastes. Developing such a MAC protocol has been a hot research area in WSN. To avoid wasting the limited energy, various energy saving mechanisms are proposed for MAC protocols. These mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 79 publications
(107 reference statements)
0
35
0
Order By: Relevance
“…A MAC protocol that implements duty cycling uses appropriate sleep/wake-up mechanisms to conserve energy, and in [22], it is demonstrated that when sensor nodes remain in the sleep mode, they consume less energy than when in the idle mode. When there is no need for communication, the radio is put to sleep and, although applying duty cycling energy is conserved, it has some disadvantages.…”
Section: Wake-up Mechanisms For Wsnmentioning
confidence: 99%
See 2 more Smart Citations
“…A MAC protocol that implements duty cycling uses appropriate sleep/wake-up mechanisms to conserve energy, and in [22], it is demonstrated that when sensor nodes remain in the sleep mode, they consume less energy than when in the idle mode. When there is no need for communication, the radio is put to sleep and, although applying duty cycling energy is conserved, it has some disadvantages.…”
Section: Wake-up Mechanisms For Wsnmentioning
confidence: 99%
“…If a node has no packet to receive, it can waste a large amount of energy by just listening to the channel. Consequently, a node can save a significant amount of energy if it simply goes to sleep mode by switching off its radios [22]. T-MAC is an improvement over S-MAC duty cycling.…”
Section: Wake-up Mechanisms For Wsnmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, asynchronous dynamic MAC protocols (Adaptive DutyCycling) used for implementing Sleep schedule in sensor nodes are considered [1], [48]. However in the second case on demand sleep scheduling protocols are considered.…”
Section: A Cluster Head Node Behaviourmentioning
confidence: 99%
“…A number of schemes have been proposed to save energy in WSNs. These include implementation of sleep schedules within MAC [1] and [2] and routing [3] protocols and also in other layers. Hardware developers have also continued to improve devices with the aim of achieving low levels of energy consumption and efficiency [4].…”
Section: Introductionmentioning
confidence: 99%